Characterization of bioparticle for wastewater treatment - Ibrahim, Zaharah; Baba, Abu Bakar; Abd. Majid, Zaiton; Yahya, Adibah (Universiti Teknologi Malaysia, 2006)
The removal of dyes and others contaminants such as heavy metals from effluent remains a major problem for the textile industry. While coloured organic compounds generally impart only a minor fraction of the organic load to wastewater, their colours renders them aesthetically unacceptable. Many dye compounds and their intermediates are carcinogenic and difficult to remove by conventional wastewater treatment methods. Many physico-chemical methods have been used for textile wastewater treatment. However, they showed some disadvantages such as high treatment cost, low efficiency to a wide range of dyes and toxic sludge generation. Bioremediation based on microbial technologies for treating textile wastewater promise satisfactory contaminants removal due to the biodegradation and mineralization of contaminants into non-toxic compounds. Therefore, this research has focused on bioremediation of textile wastewater, especially in colour and heavy metals removal, using biofilm. The potential dye-degrader and heavy metal removal bacterial strains were first isolated from textile effluents. Screening studies of isolated strains for dye decolourization and heavy metals removal were carried out using filter sterilized textile effluent and simulated textile wastewater in batch scale. Further more, the selected bacterial strains were grown as biofilm on support matrices and the biofilm were used for bioremediation of textile wastewater in lab scale experiments. The biofilm structure was examined using electron-scanning microscope (SEM). Parameters such as colour intensity, aromatic amines, COD, BOD, pH, cadmium, copper, nitrate, phosphate, sulphate content were monitored during the experiment. Generally, it was found that there are three strains of bacteria, namely Bacillus cereus, Aeromonas caviae and Aeromonas hydrophilla, showed a good performance in decolourizing and degrading dyes. Besides, they were also able to remove heavy metals such as cadmium and copper. The maximum removal efficiency in lab scale experiments for colour intensity, COD, BOD, cadmium, copper, nitrate, phosphate and sulphate were 80.0%, 71.9%, 45.5%, 52.1%, 54.1%, 98.0%, 58.5% and 59.5%, respectively. Furthermore, mechanisms for biodegradation of dye showed all of them remove colour via reduction of dyes. This was confirmed by detecting the degradation products through High Performance Liquid Chromatography (HPLC). In addition, gene responsible for desulphonation was successfully amplified via PCR from Aeromonas hydrophila and thus confirmed this strain was able to remove sulphonated dyes efficiently.